PENGARUH METODE AL-BARQY MENGGUNAKAN KARTU HURUF TERHADAP HASIL BELAJAR PENDIDIKAN AL-QUR’AN DI SD ISLAM AL-AZHAR 67 BUKITTINGGI - Yesy Rahmi Putri MZ (Adisam Publisher, 2026)
The issue in this study stems from pupils' poor learning outcomes. The results show that 65 percent of the MID pupils in the first grade at SD Islam Al-Azhar 67 Bukittinggi had scores lower than KKTP in the 2023– 2024 school year's Qur'an Education Lessons. Consequently, the Al- Barqy Method is implemented while pupils are learning. A quantitative approach characterises this research method, which is quasi- experimental in nature. This study aims to accomplish the following: (1) to research the Al-Barqy method's usage of letter cards in first-grade Qur'an classes at SD Islam Al-Azhar 67 Bukttinggi (2) In order to determine the effects of using the Al-Barqy method using letter cards in Qur'an education lessons at SD Islam Al-Azhar 67 Bukittinggi, first seat... Thirdly, we want to see how first graders at SD Islam Al-Azhar 67 Bukittinggi fare when taught the Qur'an using the Al-Barqy approach, which makes use of letter cards. Concerning the matter of being familiar with the hijaiyah letters. After applying the Al-Barqy method, the learning results increased by 58.96% according to the N-Gain value test, which was in the medium category. The interpretation was also effective, leading to the conclusion that Ha was accepted. The hypothesis test, conducted using SPSS 26 software, yielded a significance score (2-tailed) = 0.000 < α = 0.05 and a significance value (2-tailed) < α. It follows that the Al-Barqy approach to teaching Hijaiyah letters through the use of letter cards has an effect on the results of Qur'an education at SD Islam Al-Azhar 67 Bukittinggi.